2007
DOI: 10.1007/s11538-007-9220-2
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Reproduction-Dispersal Equations and Heavy Tail Dispersal Kernels

Abstract: Reproduction-Dispersal equations, called reaction-diffusion equations in the physics literature, model the growth and spreading of biological species. IntegroDifference equations were introduced to address the shortcomings of this model, since the dispersal of invasive species is often more widespread than what the classical RD model predicts. In this paper, we extend the RD model, replacing the classical second derivative dispersal term by a fractional derivative of order 1 < α ≤ 2. Fractional derivative mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 73 publications
2
58
0
Order By: Relevance
“…One of the main challenges is an implementation of the description of chemical reactions in non-Markovian transport processes governed by CTRW with non-exponential waiting time distributions. There exist several approaches and techniques to deal with this problem [2][3][4][5][6][7][8][9][10][11]. In particular, there are many efforts to incorporate the chemical reactions into subdiffusive transport.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main challenges is an implementation of the description of chemical reactions in non-Markovian transport processes governed by CTRW with non-exponential waiting time distributions. There exist several approaches and techniques to deal with this problem [2][3][4][5][6][7][8][9][10][11]. In particular, there are many efforts to incorporate the chemical reactions into subdiffusive transport.…”
Section: Introductionmentioning
confidence: 99%
“…Let u andû J be the solutions of (17)- (19) and (34)- (36), respectively. Assume that u 0 ∈ H. We have:…”
Section: Fourier Spectral Methodsmentioning
confidence: 99%
“…We note that Definitions (4) and (5) are not equivalent [17]. For the deterministic space-fractional partial differential equations where the space-fractional derivative is defined by (5), or the Riemann-Liouville space-fractional derivative, or the Caputo space-fractional derivative, many numerical methods are available, for example, finite difference methods [18][19][20][21][22][23][24][25][26][27][28][29][30], finite element methods [14,[31][32][33][34][35][36][37][38][39][40] and spectral methods [41,42]. For the deterministic space-fractional partial differential equations where the space-fractional derivative is defined by (4), some numerical methods are also available, for example the matrix transfer method (MTT) [21,22,43] and the Fourier spectral method [44].…”
Section: Introductionmentioning
confidence: 99%
“…The equation is described as (1) ∂u(x, t) ∂t = D α x u(x, t) + f (u, x, t), (x, t) ∈ Ω × (0, T ] with an initial condition (2) u(x, 0) = u 0 (x), x ∈Ω…”
Section: Introductionmentioning
confidence: 99%
“…The analytical results on existence and uniqueness of the solution for (1) have been studied by Baeumer, Kovács and Meerschaert [2] using the semigroup theory when the source term f (u, x, t) is globally Lipschitz continuous with respect to u. They have also shown that the solution exists uniquely by introducing the cut-off function when the function f (u, x, t) is locally Lipschitz continuous.…”
Section: Introductionmentioning
confidence: 99%